1993
DOI: 10.3386/w4494
|View full text |Cite
|
Sign up to set email alerts
|

Sticking it Out: Entrepreneurial Survival and Liquidity Constraints

Abstract: We examine why some individuals survive as entrepreneurs and others do not. In addition, we analyze the growth of entrepreneurial enterprises, conditional on surviving. Our focus is on the role of access to capital-to what extent do liquidity constraints increase the likelihood of entrepreneurial failure? The empirical strategy is based on the following logic: If entrepreneurs cannot borrow to attain their profit-maximizing levels of capital, then those entrepreneurs who have substantial personal financial res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
295
4
5

Year Published

2001
2001
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 454 publications
(332 citation statements)
references
References 13 publications
28
295
4
5
Order By: Relevance
“…Especially interesting is the work of Holtz-Eakin et al (1994) and Blanchflower and Oswald (1998). They also test whether personal wealth affects the decision to become an entrepreneur but using the increase in wealth deriving from inheritance and gifts.…”
Section: The Determinants Of the Occupational Choicementioning
confidence: 98%
“…Especially interesting is the work of Holtz-Eakin et al (1994) and Blanchflower and Oswald (1998). They also test whether personal wealth affects the decision to become an entrepreneur but using the increase in wealth deriving from inheritance and gifts.…”
Section: The Determinants Of the Occupational Choicementioning
confidence: 98%
“…In a study on individuals who have developed business ideas but decided against launching new ventures, Van Auken (1999) found that financial constraints were the most significant obstacle standing in the way of business launch. The resources required to form a new firm are usually beyond the means of individual entrepreneurs (Bhave, 1994) and lack of funding might be a reason for nascent entrepreneurs to abandon the start-up process (Holtz-Eakin et al, 1994). As a corollary, recent studies have ascertained that lower capital requirements and better access to capital raises the likelihood of firm formation (Van Gelderen et al, 2005).…”
Section: The Relationship Between Availability Of Financing and New Vmentioning
confidence: 99%
“…Household labor income before the transition to entrepreneurship is also included in the estimation: this variable should control for any income effect in the occupational choice. In order to a have a proxy for entrepreneurial ability, I include the possibility of learning informal business experience from the parents (Lentz and Laband 1990;Holtz-Eakin et al 1994a;Guiso and Schivardi 2005): in detail, a dummy is equal to 1 if one of the parents was self-employed. 15 Like other control variables, I also consider several household characteristics that can influence the shape of the household utility function and the occupational choice.…”
Section: The Probability Of Becoming An Entrepreneur and Initial Non-mentioning
confidence: 99%